PENGGUNAAN SCAFFOLDING UNTUK MEMPERBAIKI KESALAHAN SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA - Susilo, Claudya Zahrani (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
Abstract This research is a qualitative description research which describe scaffolding to fix the junior high students' error in solving mathematics problem. The research subject is 7th grade student which represent mathematics ability in high, medium and low level. The result shows that the students' problem are (1) error in writing information of the problem, (2) error in writing the formula that is used in solving problem, and (3) komputational error. Scaffolding is used to fix the students' problem. Those are (1) asking students to reread the problem, (2) giving directional question to students, (3)asking students to reflect their answer,and (4) asking students to recheck the result of their problem. Keywords: scaffolding, error, mathematics' problem